139k views
1 vote
H(x)=3x+4 k(x)=9-x find (h(k(x)))

User Splact
by
4.4k points

2 Answers

5 votes

Answer:

h(k(x)) = -3x + 31

Explanation:

To find h(kx)), plug in k(x) in as x in the function h(x)

h(x) = 3x + 4

Plug in k(x) as x:

h(k(x)) = 3(9 - x) + 4

h(k(x)) = 27 - 3x + 4

h(k(x)) = -3x + 31

User Justin Martin
by
4.7k points
3 votes

Answer: h(k(x))=-3x+31

Explanation:

To find h(k(x)), you want to plug k(x) into h(x).

h(k(x))=3(9-x)+4 [distribute]

h(k(x))=27-3x+4 [combine like terms]

h(k(x))=-3x+31

Now, we know that h(k(x))=-3x+31.

User MazzCris
by
5.4k points